2015
DOI: 10.1590/0104-1428.2158
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weight and tacticity effect on morphological and mechanical properties of Ziegler–Natta catalyzed isotactic polypropylenes

Abstract: SbstractThe morphological and mechanical properties of Ziegler-Natta catalyzed isotactic polypropylenes as influenced by the molecular weight and tacticity was investigated. Polypropylene samples were injection moulded into standard disks with a HAAKE MiniJet II injection moulder at 190 °C and 200 bar for morphological and mechanical tests. The morphological and mechanical properties of specimens were investigated by means of optical microscope (OM), scanning electron microscopy (SEM), microhardness (MH) and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Table reports the measured M w and PDI. The M w value is comparable with the viscosity average molecular weight, M v , of an equivalent MFR i ‐PP reported in the literature …”
Section: Methodssupporting
confidence: 87%
“…Table reports the measured M w and PDI. The M w value is comparable with the viscosity average molecular weight, M v , of an equivalent MFR i ‐PP reported in the literature …”
Section: Methodssupporting
confidence: 87%
“…Nonpolar polymers are characterised by an appropriate range of molecular weights between critical values, whereas polar polymers and polymers containing hydrogen exhibit optimal mechanical properties at low molecular weights [48], [49]. The dielectric films used in capacitors, however, must have sufficient tensile strength to withstand the pressure applied on the film layer when they are rolled tightly to prevent air gap formation.…”
Section: B Mechanical Propertiesmentioning
confidence: 99%
“…Comparing the effects of AC and DC voltage on discharge events shows that the amount of discharge under DC voltage is considerably less than that under the AC voltage on the assumption that the dielectric films have the same properties and are subject to the same measurement conditions [49]. The PD events under both AC and DC voltages heavily depend on the film thickness where a void size inside dielectric relates to the random nature of the polymers.…”
Section: ) Under Ac Voltagementioning
confidence: 99%
“…For example, Menyhard et al and Ksmael et al examined the effects of stereoregularity and molecular weight on the physical properties of PPs produced using heterogeneous Ziegler-Natta (ZN) catalysts. [6,7] PP samples with different stereoregularities and molecular weights were prepared using different catalysts or external donors, and their dependence on the physical properties was examined. De Rosa et al and Minami et al prepared PP samples with precisely controlled stereoregularity using diverse molecular catalysts, and showed that their thermal and mechanical properties were correlated with stereo-defects.…”
Section: Introductionmentioning
confidence: 99%